1982
DOI: 10.1007/bf01850987
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 3′-Methyl-4-dimethylaminoazobenzene on liver cells from adult rat in primary culture

Abstract: Primary mass cultures of isolated liver cells, which prepared from normal adult rat by a collagenase-liver-perfusion technique, were treated with 3'-methyl-4-dimethylaminoazobenzene (3'-Me-DAB) to study the production of transformed liver cells. Enzymatically isolated liver cells had high sensitivity to 3'-Me-DAB in primary culture. By 2- or 6-day treatment, mature hepatocytes remarkably decreased in their numbers due to cytotoxic effect of 3-Me-DAB, but thereafter active proliferation of epithelial-like clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Since it has been reported that the gamma-GTP activity per cell was independent of cell density (Sakakibara and Tsukada, 1980), the assay for gamma-GTP was carried out on the cultures in confluent state. As reported previously (Miyazaki et al, 1982), the cytochemical assay for gamma-GTP on the cultures fixed with cold acetone was carried out according to the method of Albert et al (1961) using N-gamma-L-glutamyl-alphanaphthylamide (Sigma Chemical Co., St. Louis, MO, USA) as a substrate, fast garnet GBC salt (Sigma Chemical Co., St. Louis, MO, USA) as a diazonium coupling reagent and glycylglycine (Sigma Chemical Co., St. Louis, MO, USA) as an acceptor for acceleration of the enzymatic reaction. Nuclei of cultured cells were stained with hematoxylin.…”
Section: Cytochemical Assay For Gamma-gtpsupporting
confidence: 64%
“…Since it has been reported that the gamma-GTP activity per cell was independent of cell density (Sakakibara and Tsukada, 1980), the assay for gamma-GTP was carried out on the cultures in confluent state. As reported previously (Miyazaki et al, 1982), the cytochemical assay for gamma-GTP on the cultures fixed with cold acetone was carried out according to the method of Albert et al (1961) using N-gamma-L-glutamyl-alphanaphthylamide (Sigma Chemical Co., St. Louis, MO, USA) as a substrate, fast garnet GBC salt (Sigma Chemical Co., St. Louis, MO, USA) as a diazonium coupling reagent and glycylglycine (Sigma Chemical Co., St. Louis, MO, USA) as an acceptor for acceleration of the enzymatic reaction. Nuclei of cultured cells were stained with hematoxylin.…”
Section: Cytochemical Assay For Gamma-gtpsupporting
confidence: 64%
“…As reported previously, liver cells were isolated from adult rats by trypsin and collagenase perfusion techniques [15,17]. The perfusate used in this study were as follows.…”
Section: Preparation and Primary Culture Of Isolated Liver Cellsmentioning
confidence: 99%
“…Similar doses of AO were found to be cytotoxic in Sertoli germ cells (Mishra et al 2009); and for BY in primary hepatocytes (Miyazaki et al 1982). Significant loss of membrane integrity and leakage of LDH in the medium was observed by AO and BY in a dose-and time-dependent manner.…”
Section: Discussionmentioning
confidence: 90%